Gun culture in early modern England - Schwoerer, Lois G. (University of Virginia Press, 2016)
"This volume identifies, describes, and analyses early modern England's gun culture. It explains how guns became available to men, women, and children of all social standings, how subjects responded to guns, how firearms changed their lives, how the government reacted to civilians possessing guns, and the role of guns in the settlement of the Revolution of 1688-89. Elite men used guns for hunting, target-shooting, and protection. They collected guns and included them in portraits and coats-of-arms, regarding firearms as a mark of status, power, and sophistication. Unlike their European counterparts, English ladies did not embrace the gun in hunting and target shooting, but they used them in the Civil Wars and in acts of violence. Little boys, across the social spectrum, played with toy guns. The government denied firearms to subjects with an annual income under £100--about 98 percent of the population, which showed resentment by grudging acceptance to willful disobedience. They used guns to hunt for food, not sport, and saw no crime in poaching. The gun industry contributed to the economy. The Ordnance Office, the government's department charged with military matters, employed aristocrats as officers, men of middling status as master gunners, and plebeian men and women, mostly widows, to make and repair guns. Guns were featured in the 1689 Bill of Rights, but it did not, as some scholars aver, grant individual Protestants a right to bear arms. So it cannot be cited to support the claim that the Second Amendment to the U.S. Constitution conveys such a right as an Anglo-American legacy"--Provided by publisher.